Hydrothermal and energy analysis of flat plate solar collector using copper oxide nanomaterials with different morphologies: Economic performance. (February 2022) - Alawi, Omer A.; Kamar, Haslinda Mohamed; Abdelrazek, Ali H.; Mallah, A.R.; Mohammed, Hussein A.; Ibrahim Abdulla, Aziz; Alwan Gatea, Hamed; Khiadani, Mehdi; Kazi, S.N.; Yaseen, Zaher Mundher
Abstract: Flat plate solar collectors (FPSCs) have gotten a lot of attention in the last decade because of their ease of installation and design. The current study focused on numerical aspects of a three-dimensional (3D) inclined tube-on-absorbing sheet solar collector. The numerical model was considered to work under a conjugated laminar mixed convection heat transfer mechanism in the range of 100 ≤ Re ≤ 1300. CuO/H2 O nanofluids were used as the working fluids. The impact of different parameters on the thermal efficiency of the current FPSC, including inlet temperature, nanoparticle size, volume concentration, and various copper oxide morphologies, on the heat transfer, thermodynamics, thermal, and economic performance, was studied. According to simulation results, the solar collector using distilled water (DW) under 293 K performed better in terms of heat transfer and energy efficiency than those using 303 K and 313 K. In comparison to other sizes and volume concentrations, nanosphere nanofluids with 20 nm and 4% showed higher hydrothermal performance characteristics. Nanoplatelets-shaped CuO nanofluids illustrated the higher values for pressure drop, heat transfer, energy gain, energy efficiency, and lower values for surface plate temperature and outlet temperature, followed by nanocylinders, nanoblades, nanobricks, and nanospheres, respectively. The economic performance indicators recommended that nanobricks CuO nanofluids with 1% volume fraction were the best fluid replacement for water in solar collector applications.